2021
DOI: 10.1002/agg2.20132
|View full text |Cite
|
Sign up to set email alerts
|

Forage species and summer management impacts on soil carbon and nitrogen in winter stockpiled grazing systems

Abstract: Soil organic matter (SOM) in managed grasslands have economic and environmental benefits. This experiment evaluated a stockpiled winter grazing system with two summer management treatments (grazing or hay harvest) and three forage species treatments: tall fescue (TF, Schedonorus arundinaceus Schreb.), switchgrass (SG, Panicum virgatum L.), and mixed big bluestem–Indiangrass [BBIG, Andropogon gerardii Vitman–Sorghastrum nutans (L.) Nash]. Soil was sampled on 18 dates (January 2016–July 2017) at two depths (0–5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Forage species and cropping systems also play a major role in controlling soil C accumulation (Allen et al, 2006; Rolando et al, 2021; Tilhou et al, 2021; Wang et al, 2014). Wang et al (2014), evaluating the effects of grass species and grazing intensity on soil C in North Carolina, reported that after 4 years, soils cultivated with annual ryegrass/sorghum–sudangrass contained ~20% more C (0–10 cm) than soils under annual ryegrass/bermudagrass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forage species and cropping systems also play a major role in controlling soil C accumulation (Allen et al, 2006; Rolando et al, 2021; Tilhou et al, 2021; Wang et al, 2014). Wang et al (2014), evaluating the effects of grass species and grazing intensity on soil C in North Carolina, reported that after 4 years, soils cultivated with annual ryegrass/sorghum–sudangrass contained ~20% more C (0–10 cm) than soils under annual ryegrass/bermudagrass.…”
Section: Discussionmentioning
confidence: 99%
“…This response was associated with greater above‐ and belowground biomass under N‐fertilized pastures, which likely favored soil C accumulation. In a 3‐year study in Tennessee, Tilhou et al (2021) evaluated C pools in stockpiled winter grazing systems with two summer management treatments (grazed or hayed) and three plant species (tall fescue, switchgrass, or a mixture of Indian grass and big bluestem). The authors reported that both the defoliation regimen and plant species affected soil C concentrations (0–5 cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in soil health and fertility including biological degradation (organic matter) is a worrying trend and has the potential to lower productivity significantly. Constant monitoring of soil health status is an essential factor in processes of development of land management systems that ensure the sustainability of soil resources (Tilhou et al, 2021). In order to reclaim the damage to soil and ensure global agricultural sustainability, the identification of these stressors as well as development of sustainable methods such as bioremediation is important (Tahat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%